The influence of the guide vane angle of the turbocharger on the turbine mechanical properties and flow field characteristics. (August 2019) - Zhang, Shiqiang; Li, Chunshu; Fan, Liwei
Abstract: Turbocharged gasoline engines produce less exhaust gas when running at a low speed, which is not enough to make the turbine rotor run at a high speed and press in enough air. By changing the cross-section area of the exhaust gas inlet and controlling the gas flow velocity, the turbine can achieve a larger rotation speed with less exhaust gas. Croe2.0 3D software was used to build the 3D model of the adjustable turbine device. ANSYS software is used to analyze the stress of turbocharger turbine. By adjusting the gas flow rate, the adjustable turbine device can significantly change the numerical value of the turbine force, which improves the problems faced by turbocharging engine at low speed and provides theoretical basis for the adjustable turbocharging technology.